Instrument Response of the Indonesian People’s Accelerograph (ARI) Type I Based on MEMS Sensor MPU6050 - Akram, Rafi Syah; Satrio, Adji; Sutejo, Bayu; Martha, Agustya Adi; Widodo, Handi Sulistyo; Nugroho, Hapsoro Agung; Prakoso, Tio Azhar; Hudayat, Nurul (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2025)
The Indonesian Peopleâ€™s Accelerograph (ARI) is an innovative ground motion recording device developed using predominantly local, cost-effective components to accurately monitor and record seismic-induced ground acceleration for disaster mitigation. This study aimed to evaluate the instrument response of ARI Type I, which utilizes a MEMS sensor (MPU6050) to capture dynamic acceleration data crucial for earthquake early warning systems. The research involved a comprehensive methodology comprising hardware design, field testing, and in-depth analysis of the instrumentâ€™s response by determining key parameters such as gain, poles, and zeros under various seismic conditions. The hardware was meticulously designed using KiCAD, with the final assembly enclosed in a 3D-printed casing that integrates the ESP32 microcontroller, sensor, SD card, and LCD, while data communication was achieved via I2C and WiFi protocols, and time synchronization was maintained using NTP. Field tests conducted at the UNILA site demonstrated that ARI Type I records ground acceleration on all three axes at a density of 50 signals per second. Data retrieved and processed through Python into a DataFrame confirmed the systemâ€™s high sensitivity and reliability, with a measured gain of approximately 3637.48 V/g, poles of 1.39133434Ã—10â»â¸ and 9.10426934Ã—10â»Â², and zeros of â€“1.52128433Ã—10â»â¶ and â€“4.69561707Ã—10Â³. These promising results validate the potential of ARI Type I as an effective tool for seismic monitoring, contributing to the development of robust early warning systems and enhancing disaster resilience in earthquake-prone regions.